1991
DOI: 10.3109/08990229109144743
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Corticocortical Projections of Rat Somatosensory Cortex

Abstract: Rhodamine-coated microspheres (RCMs) were injected into the primary somatosensory cortex (SI) of rats ranging in age from postnatal (PN) day 1 to adulthood. Ipsilateral corticocortical and callosal projections within the SI were identified as early as PN day 1. At the end of the first PN week, ipsilaterally projecting neurons located in sublayer VIb were the first to assume an adult-like pattern of connectivity. Injections at subsequent postnatal ages revealed that an adult pattern of lamination of ipsilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
(32 reference statements)
1
19
0
Order By: Relevance
“…The widespread tangential extent of the labeling pattern from subgriseal neurons is consistent with results of some previous studies (Nicolelis et al, 1991) but does not support earlier descriptions of a probable columnar organization for portions of these neurons (Divac et al, 1987;Reep and Goodwin, 1988). Continuous labeling, clusters of 1-10 labeled subgriseal cells, and single-labeled subgriseal cells were found rostrocaudal and lateromedial to the application sites.…”
Section: Widespread Labeling Of Subgriseal Neurons In Ipsilateral Hemsupporting
confidence: 80%
See 1 more Smart Citation
“…The widespread tangential extent of the labeling pattern from subgriseal neurons is consistent with results of some previous studies (Nicolelis et al, 1991) but does not support earlier descriptions of a probable columnar organization for portions of these neurons (Divac et al, 1987;Reep and Goodwin, 1988). Continuous labeling, clusters of 1-10 labeled subgriseal cells, and single-labeled subgriseal cells were found rostrocaudal and lateromedial to the application sites.…”
Section: Widespread Labeling Of Subgriseal Neurons In Ipsilateral Hemsupporting
confidence: 80%
“…This distinction may be important because in mammals both layer I and subgriseal neurons are believed to develop fully prior to the development of neurons in layers II-VI (layer I is the first formed cortical layer; layer II, although directly subjacent, is the last generated layer; Bayer and Altman, 1990), and subplate connections to layer I form one of the first functional cortical relationships (Ramon y Cajal, 1955;Marin-Padilla, 1978;Kristt, 1979b;Chun et al, 1987;Friauf et al, 1990;Nicolelis et al, 1991). Nevertheless, it has commonly been believed that this subplatelayer I connection is lost in the mature cortex (MarinPadilla, 1998).…”
Section: Connections From Subgriseal Neurons To Cortical Layer I In Mmentioning
confidence: 99%
“…This study confirms that the projection from zona incerta to layer I of SI can be labeled by using other fluorescent tracers and that HRP does not label these cells. Similarly, Nicolelis et al (1991) found neurons in a dense band at the border between the dorsolateral cortex and the white matter following retrograde transport of fluorescent tracers from SI. Likewise, we find that these cells project to layer I of SI with the use of fluorescent tracers but not with HRP (Clancy and Cauller, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The collaterals of layer II/III and V pyramidal cells have been found to provide long-range horizontal connections in those layers in a number of species and cortical areas including rat somatosensory cortex. 7,22 Interlaminar connections between layers II/III and V have also been described in rat somatosensory cortex. 5 The presence of long-range horizontal connectivity in layer VI similar to that observed in layers II/III and V has been documented in the somatosensory cortex of the rat using a number of different labeling techniques including rhodamine-coated microspheres 22 and biocytin.…”
Section: Comparison With Other Anatomical Neurophysiological and Opmentioning
confidence: 99%
“…7,22 Interlaminar connections between layers II/III and V have also been described in rat somatosensory cortex. 5 The presence of long-range horizontal connectivity in layer VI similar to that observed in layers II/III and V has been documented in the somatosensory cortex of the rat using a number of different labeling techniques including rhodamine-coated microspheres 22 and biocytin. 30 Projections from layer VI to layer IV are also known to exist, although whether they target predominantly inhibitory or excitatory interneurons has been a subject of debate.…”
Section: Comparison With Other Anatomical Neurophysiological and Opmentioning
confidence: 99%